Системна формалізація процесів розвитку кіберспорту в Україні - Чизмар Іван; Csizmár Iván; Chyzmar Ivan (Видавничий дім «Гельветика», 2021)
Резюме. У статті представлено специфіку системної формалізації процесів розвитку кіберспорту в Україні. За отриманими результатами виявлено значну кількість кіберспортсменів Dota2, CS:GO, що працюють поза клубною системою. Доведено потребу забезпечення розвиту клубної системи кіберспорту за дисциплінами Valve Corporation в Україні за рахунок заходів із техніко-економічного розвитку кіберспортивних клубів, максимізації їхніх доходів. Формалізація процесів розвитку кіберспорту за підсистемою Valve Corporation виявила формування ресурсів із розширення виробництва лише по кіберспортивних продуктах Dota2, CS:GO. За іншими іграми розробника/видавця формування ресурсів із розширення виробництва та значний розвиток малоймовірні. Для активізації процесів формування ресурсів із розширення виробництва за підсистемою Valve Corporation необхідне розширення функції прибутку. Формалізація процесів розвитку підсистеми кіберспортивних подій виявила, що незалежні турнірні оператори України орієнтовані на розширення виробництва кіберспортивного продукту Home Game.

Abstract. Ukraine is one of the top countries in the world in the development of cybersports, so it is important to identify the current features of the development of the defined area of the Ukrainian digital economy and to formalize the outlined processes. There-fore, the article singles out and logically present the system formalization of processes of development of cybersport in Ukraine through its subsystems. In particular, the logic of formalization of processes of development of cybersport as a system is highl ighted and studied; the logic of formalization of processes of development of cybersport through its F-operands is presented. The result was the testing of the logic of formalization of processes of development of cybersport on subsystems. During the testing process, the formalization of cybersports development actions was implemented on the subsystem of Valve Corporation, which revealed the formation of resources to expand production only for Dota2, CS: GO cybersports products. For the rest of the developer/publisher games, the generation of expansion resources and substantial development is unlikely. The expansion of the profit function is necessary in order to increase the growth of the Valve Corporation’s expansion resources. The formal-ization of the development processes of the cybersports events subsystem has shown that independent tournament operators of Ukraine are oriented on the expansion of production of the cybersports product Home Game in the format of Internet LAN Party. In order to create resources to expand the production of cybersports events, it is advisable to expand their list of Internet LAN Party, Loud Party, and LAN Area-Party (since now mostly home online show matches). As part of the test, a significant number of Dota2 and CS: GO cyber athletes were found working outside the club system. It has been proved necessary to ensure the development of the club system of cybersports in the disciplines of Valve Corporation in Ukraine by means of measures on tech-nical and economic development of cybersports clubs and maximization of their earnings. Further prospects in this direction lie in the use of the logic of formalization of processes of development of cybersport as a system through F-operands to form a model of activation of processes of its development in Ukraine.
System formalization of cybersport development processes in Ukraine
Редакційна колегія: https://ev.fmm.kpi.ua/editorial
Зміст: https://ev.fmm.kpi.ua/issue/view/15170
Keywords: формалізація; процеси розвитку; кіберспорт; кіберспортивні події; рівняння; F-операнди